Sistem za spremljanje in optimiranje postopka frezanja z uporabo genetskih algoritmov - Milfelner, Matjaž (Strojniški vestnik, 2004)
This paper presents a system for monitoring and optimizing the ball-end milling process. The system combines different methods and technologies, like evolutionary methods, manufacturing technology, measuring and control technology and intelligent process technology with the appropriate hardware and software support. The system for monitoring and optimizing the ball-end milling process combines the process monitoring system of the ball-end milling process and the optimization model. The monitoring system is designed for monitoring and collecting the variables of the milling process by means of sensors and the transformation of those data into numerical values, which are the starting point for the optimization of the ball-end milling process. The optimization model is used for the optimization of the milling parameters with genetic algorithms. The optimization is based on the analytical cutting-force model and the tool-wear model. The developed methods can be usedfor the cutting-force estimation and the optimization of the cutting parameters. The integration of the proposed system will lead to a reduction inthe production costs and production time, flexibility in machining-parameter selection, and an improvement in product quality.
Keywords: optimiranje odrezavanja; sile rezanja; parametri rezanja; frezala oblikovna krogelna; algoritmi genetski; odrezavanje; optimiranje; genetski algoritmi